2006
DOI: 10.1063/1.2210937
|View full text |Cite
|
Sign up to set email alerts
|

A Hirshfeld partitioning of polarizabilities of water clusters

Abstract: A new Hirshfeld partitioning of cluster polarizability into intrinsic polarizabilities and charge delocalization contributions is presented. For water clusters, density-functional theory calculations demonstrate that the total polarizability of a water molecule in a cluster depends upon the number and type of hydrogen bonds the molecule makes with its neighbors. The intrinsic contribution to the molecular polarizability is transferable between water molecules displaying the same H-bond scheme in clusters of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
115
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(124 citation statements)
references
References 54 publications
6
115
0
Order By: Relevance
“…Numerous studies have demonstrated the difference in molecular polarizability between molecules in the gas and condensed phases. [49][50][51] The TIP4P-QDP model of Bauer et al 52 introduces phase-dependent polarizability into a classical simulation. The electrostatic component of the Hamiltonian is modified such that the and parameters are functions of the M-site ͑lone-pair site͒ charge,…”
Section: B Phase-dependent Polarizable Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have demonstrated the difference in molecular polarizability between molecules in the gas and condensed phases. [49][50][51] The TIP4P-QDP model of Bauer et al 52 introduces phase-dependent polarizability into a classical simulation. The electrostatic component of the Hamiltonian is modified such that the and parameters are functions of the M-site ͑lone-pair site͒ charge,…”
Section: B Phase-dependent Polarizable Modelmentioning
confidence: 99%
“…[49][50][51] Generally accepted reductions fall either in the range of 7%-10% or 30%. Using the Hirshfeld partitioning scheme and density functional theory calculations, Krishtal et al 50 explored the dependence of polarizability on water cluster size. They reported that the intrinsic molecular polarizability decreases with increasing cluster size, converging to a bulklike value in the limit of a significantly large cluster ͑n H 2 O =20͒.…”
Section: Introductionmentioning
confidence: 99%
“…31 Recently, the fuzzy Hirshfeld partitioning scheme of the electron density has also been applied to extract molecular polarizabilities in clusters 32,33 or atomic polarizabilities in large molecular systems. 9 However, a disadvantage of the Hirshfeld scheme, at least in the current implementations, is that the functional-group polarizabilities remain origin-dependent and, therefore, cannot be properly exported to other systems.…”
Section: Introductionmentioning
confidence: 99%
“…36 It is especially encouraging that the SQE model exhibits a transition between the EEM-like polarizability scaling for small systems to the linear scaling for extended systems, 34,36 as is often observed in computational studies. 13,[37][38][39][40] Since the primary goal of all CPE-based models is the fast and reliable computation of charge distribution in large systems, the parameterization of such a model is done by fitting atomic charges produced by the model to those derived from quantum-chemical calculations. The problem is that the atomic charge is not a quantum-chemical observable 41 and consequently, many electronic density partitioning schemes can be used to produce the reference charge values.…”
Section: Introductionmentioning
confidence: 99%